-1又2分之1-[-3分之1]+6分之1-1又4分之1=?怎么算.
2个回答
-1又2分之1-[-3分之1]+6分之1-1又4分之1
=-3/2+1/3+1/6-5/4
=-18/12+6/12+2/12-15/12
=-25/12
相关问题
1993又2分之1-1992又3分之1+1991又2分之1-1990又3分之1+……+1又2分之1-3分之1 怎么算
1又2分之1+2又4分之1+3又8分之1+4又16分之1+5又32分之1+6又64分之1
31又2分之1*3分之2+41又3分之1*4分之3+51又4分之1*5分之4+61又5分之1*6分之5+71又6分之1*
1又6分之1+2又12分之1+3又20分之1+4又30分之1+5又42分之1+6又56分之1
(-12又3分之2)/1又4分之1-(-8又3分之1)/(-1又4分之1)+(+20又3分之1)/1又4分之1
1又2分之1+2又6分之1+3又12分之1+4又20分之1……+20又420分之1=()
(2又12分之5 3又8分之5 4又6分之5)/(2又12分之1 3又8分之1 4又6分之1)如何巧算
10分之1乘(-3又2分之1)除以(-7又6分之1) 怎么算
-1又2分之1+1又3分之1+(-5/6)=?②3又2分之1+|-2又4分之1|+(-1/3)-0.25+|+1/6|=
1又2分之1. 1又4分之1. 3又6分之3. 1又5分之3 4又3分之2的倒数是多少